Analisis Efektivitas dan Efisiensi Anggaran Belanja Langsung (Studi Kasus Pada Dinas Sosial Kota Bandung) - Putri Febrianty; Ira Novianty; Etti Ernita Sembiring (Indonesian Accounting Research Journal, 2021)
This research was conducted at the Bandung City Social Service, this study aims to analyze how the effectiveness and efficiency of the budget is implemented. The object of this research is the realization of the direct expenditure budget from 2016-2020 which is the main component in implementing programs and activities. This research is a qualitative research using a case study approach. Data collection techniques used are interviews and documentation. Sources of data used in this reseacrh are primary data derived from interviews with predetermined sources and secondary data derived from Budget Realization Reports and Performance Reports of Government Agencies of the Bandung City Social Service. This research uses quantitative descriptive data analysis techniques by calculating the level of effectiveness and efficiency which then the results are analyzed. The results showed that in 2016-2020 the average level of effectiveness of the direct expenditure budget of the Bandung City Social Service was only 78.09% which entered the criteria of being less effective, this was because the Social Service had not been able to realize its budget optimally and the programs and activities that has not been able to have a long-term impact on society. In terms of efficiency in 2016-2020 the average level of efficiency of the direct expenditure budget is 76.57%, which is included in the efficient criteria, the Social Service in this case has been able to implement budget efficiency by making alternatives that can reduce inputs or costs, without affecting.